Generative artificial intelligence and the risk of technodigital colonialism - Leonardo Cambraia; Monique Pyrrho (Frontiers in Political Science, 2025)
The use of Generative Artificial Intelligence has raised concerns related to plagiarism in scientific contexts. However, bad academic writing is far from being the main ethical challenge related to digital transformations in knowledge production. Additionally, science is not the only trust discourse affected, as journalism and law are deeply impacted in its social roles by the dissemination of artificially generated discourses. Power and knowledge are increasingly imbricated in digital society in a global context where colonial hierarchization, dehumanization and exploitation strategies are still in place. In response to the insufficiency of high-level moral principles before the ethical and Human Rights challenges brought by GenAI applications, this paper offers an alternative theoretical approach to digital ethics presented in the “decolonizing ethical thinking” section. The aim is to focus on the role that the new epistemic dynamics play to the risk of technodigital colonialism. Decoloniality readings should account for why the benefits and risks are not universally distributed and therefore may help ethical responses be more attentive to the connections between knowledge and power.